Micropygomyia (Coquillettimyia) nahua sp. nov., a new Phlebotominae sand fly from Mexico (Diptera, Psychodidae) - Ibáñez-Bernal, Sergio; García-Torres, Carlos Roberto; Vásquez-Márquez, Mario (Zootaxa, 2017)
Micropygomyia (Coquillettimyia) nahua sp. nov., is described and illustrated based on male and female characteristics. Specimens were collected in the Municipality of Naolinco, state of Veracruz, Mexico. This new species of phlebotomine sand fly has characteristics corresponding to the series vexator Fairchild of Galati, with male similar to Micropygomyia (Coquillettimyia) apache (Young & Perkins), Mi. (Coq.) oppidana (Dampf) and Mi. (Coq.) vexator (Coquillett), but recognized by the male paramere structure and simple apex of aedeagal ducts in the male, the later exception for this species series. Female can be confused with Mi. (Coq.) vexator, Mi. (Coq.) oppidana and Mi. (Coq.) apache, but is distinguishable by the cibarial armature combined with the long and very slender individual spermathecal ducts. Keys for male and female species of Micropygomyia (Coquillettimyia) are provided.